The governance of online expression in a networked world - Carrapiço, Helena; Farrand, Benjamin (Routledge, Taylor & Francis Group, 2016)
The purpose of this edited volume is to reflect on how Internet-related technologies, mechanisms and techniques may be used as a means to enable expression, but also to restrict speech, manipulate public debate and govern global populaces